Development of Inverce Matrix Module Related to Student’s Mathematical Connection Skills - Fadlurrochman, Rizqon Fuadi; Sumartana, Ammar Hanif; Apriyanti, Leni; Piliang, Anita Safitri; Sulastri, Yayu Laila; Ahmatika, Deti; Kosasih, Usep (Journal of Instructional Mathematics, 2022)
The purpose of this study was to describe the process and results of the development of the matrix Inverce module related to students' mathematical connection skill, as well as to describe the quality of the matrix Inverce module in terms of validity and practicality. The method used was design research with Plomp model, includes the initial research stage, development stage, and assessment stage. The data was obtained from interview, document analysis, and questionnaire. The result of this study showed that developed module was valid based on validation of material experts, media experts, and practitioner. The validation results of this module show that this module was quite feasible to use with a percentage of 80.83% from material experts and 75.93% from media experts, and was quite practical to use with a percentage of 76.90% from the educator's response questionnaire. From the validation results and educator responses, this module can be implemented as a learning resource or teaching material. In conclusion, the Inverce matrix module was declared fit and practical to be used as teaching material and learning resources.